Vertebral Bone Density Variations in Scoliotic vs. Non-Scoliotic Juveniles, and Its Implications for Schmorl's Node Development: A CT-Based Analysis Using the New Mexico Decedent Image Database - Ellen Shakeshaft; Matteo Borrini; Constantine Eliopoulos (MDPI AG, 2024)
Scoliosis, characterized by an abnormal lateral curvature of the spine, is predominantly idiopathic, underscoring the need to delve into its underlying causes for effective treatment and preventive strategies. This study investigates a potential correlation between scoliosis and Schmorl's nodes (intervertebral disc herniations) influenced by Wolff's law, which posits that bones adapt to external pressures. We analyzed CT scans from 108 juvenile decedents, including 56 with scoliosis and 52 without. After running multiple statistical tests, there was no significance between the mean bone density when compared to having scoliosis. An independent t-test provided a t-value of 0.041, which, when compared to the original significance level of 0.05, is statistically significant, although weak. When compared to the Bonferroni correction level of 0.008, it throws out the significance to give a result of not being statistically significant. It was the same in the cases of L3 (t = 0.103), L2 (t = 0.084), and L1 (t = 0.053). If compared to the regular significance level of 0.05, T12 (t = 0.012) and T11 (t = 0.042) had weak significance, but that was then excluded when the Bonferroni correction was applied. When looking at any significance of densities in different vertebral regions, the results from a one-way ANOVA (p-value = 0.213) suggest that it is likely that the results are due to random variability or chance, and that there is no statistical significance. With a value of 0.273 from a Chi-squared (χ2)/Fisher's exact test, it suggests that there is no statistically significant correlation or difference between the variables of scoliosis and Schmorl's nodes. The general pattern seems to follow that as the spine ascends, the density increases, and this is true in both scoliotic and non-scoliotic individuals. As a whole, it is evident that those with scoliosis have a lower vertebral density than those without, in all of the vertebral regions. There is, however, a weak negative linear relationship between bone density and age in both scoliotic and non-scoliotic individuals. A p-value of −0.229 obtained from a Pearson correlation coefficient analysis in non-scoliotic individuals, as well as a p-value of −0.069 in scoliotic individuals, was obtained. Overall, the findings of this study are comparable to some existing studies on similar topics, but there are few results that hold statistical significance and so this would be interesting to research further, potentially using a different dataset or a larger sample size that is more representative.